If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 6y = -1 Solving 8x + 6y = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 8x + 6y + -6y = -1 + -6y Combine like terms: 6y + -6y = 0 8x + 0 = -1 + -6y 8x = -1 + -6y Divide each side by '8'. x = -0.125 + -0.75y Simplifying x = -0.125 + -0.75y
| 9z=5z-15 | | .15x+.25(x+130)=63 | | -4(w+7)-(-7w-3)=2w | | 16x+9-4=12x+6 | | -3m(m+3)+2(m+3)= | | 3x-4y=-4 | | -x^2=5x | | 4x^2+16=16 | | Y=(x+3)(x^2+8x+15) | | 20x^3-12x=0 | | 56o=86 | | -3(3y+5)-11=-6(y+6)+3y | | 101=(2x+6) | | 4x^2+20x-8=0 | | 5a-6c=n | | 10x+5=2x-9 | | 82=(5x-40) | | -15c+4a=m | | 0=8x^2-14x | | 2g+12=3G-1 | | 5+-3a=n | | 61=(94x-20) | | 15x-120=6x-90 | | 2y-8x=-18 | | -.30(x-9)=-.50 | | 7x-(2x+7)=8x-46 | | 8+8=a | | (3x+18)(3x+18)=36 | | 4-2a=m | | 3x^2-12x+2x-8= | | 8x-(4x+6)=10 | | (3n+2)=0 |